(untitled) (Journal of Naval Architecture and Marine Engineering, 2013)
A commercial CFD code Fluent 6.3® is used to simulate non-linear free surface flow and compute the impact load during variable velocity water entry of 2D wedge and ship section. The code uses the finite volume method to solve the conservation of mass and momentum equations to obtain simulated flow field. The interface between water and air was modeled using volume of fluid (VOF) method. Wedge section with 30 degree dead-rise angle and a ship section are numerically simulated. Time history of impact force and pressures at distinct locations are predicted; and compared with existing experimental results and other numerical methods. Present numerical results compare well with experimental measurements. DOI: http://dx.doi.org/10.3329/jname.v10i1.14383